The Cashflow Quadrant Panduan Ayah Kaya Menuju Kebebasan Finansial Robert T Kiyosaki bersama Sharon L.Lechter CPA,alih bahasa,Rina Bantaran - KIYOSAKI, Robert T; LECHTER CPA, Sharon L; BANTARAN, Rina (Gramedia Pustaka Utama, 2003)
vii,330 hlm ilus 23 cm